An enhanced in vivo stable isotope labeling by amino acids in cell culture (SILAC) model for quantification of drug metabolism enzymes. - FALLON, PADRAIC (My University, 2015)
Many of the enzymes involved in xenobiotic metabolism are maintained at a low basal level and are only synthesized in response to activation of upstream sensor/effector proteins. This induction can have implications in a variety of contexts, particularly during the study of the pharmacokinetics, pharmacodynamics, and drug-drug interaction profile of a candidate therapeutic compound. Previously, we combined in vivo SILAC material with a targeted high resolution single ion monitoring (tHR/SIM) LC-MS/MS approach for quantification of 197 peptide pairs, representing 51 drug metabolism enzymes (DME), in mouse liver. However, as important enzymes (for example, cytochromes P450 (Cyp) of the 1a and 2b subfamilies) are maintained at low or undetectable levels in the liver of unstimulated metabolically labeled mice, quantification of these proteins was unreliable. In the present study, we induced DME expression in labeled mice through synchronous ligand-mediated activation of multiple upstream nuclear receptors, thereby enhancing signals for proteins including Cyps 1a, 2a, 2b, 2c, and 3a. With this enhancement, 115 unique, lysine-containing, Cyp-derived peptides were detected in the liver of a single animal, as opposed to 56 in a pooled sample from three uninduced animals. A total of 386 peptide pairs were quantified by tHR/SIM, representing 68 Phase I, 30 Phase II, and eight control proteins. This method was employed to quantify changes in DME expression in the hepatic cytochrome P450 reductase null (HRN) mouse. We observed compensatory induction of several enzymes, including Cyps 2b10, 2c29, 2c37, 2c54, 2c55, 2e1, 3a11, and 3a13, carboxylesterase (Ces) 2a, and glutathione S-transferases (Gst) m2 and m3, along with down-regulation of hydroxysteroid dehydrogenases (Hsd) 11b1 and 17b6. Using DME-enhanced in vivo SILAC material with tHR/SIM, therefore, permits the robust analysis of multiple DME of importance to xenobiotic metabolism, with improved utility for the study of drug pharmacokinetics, pharmacodynamics, and of chemically treated and genetically modified mouse models.
PUBLISHED
Keywords: SILAC; Immunology, Inflammation & Infection